E-Katalog Sebagai Sistem Informasi Pemasaran Kopi Sapit Berbasis Web - Yulistina, Dina; Arianti, Baiq Desi Dwi (Jurnal Pendidikan Informatika (EDUMATIC), 2019)
This studyaims to develop e-catalog as a web-based marketing information system for Sapit coffee and to determine the feasibility of e-catalog marketing of sapit coffee. This type of research uses the method of R&D (Research and Development). The feasibility trial of the learning media was carried out by 2 media experts and 2 material experts, as well as 20 visitors to the web-based sapit coffee marketing e-catalog. Obtained the percentage of eligibility from media experts by 71% by looking at 3 aspects, namely the appearance of the media, functionality, and visual communication so that it is declared "Eligible". The percentage of eligibility from material experts was 93% by looking at 3 aspects namely content design, content, and communication language so that it was declared "Very Eligible". The results of trials on e-catalog visitors totaling 20 people obtained the percentage of eligibility results of 67% by looking at 4 aspects namely usability, information quality, interaction quality, and user satisfaction so that it was declared "Eligible" to be used as a coffee marketing website.